2015
DOI: 10.1371/journal.pone.0139995
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Outer Membrane Protein OprD2 in Carbapenem-Resistance Mechanisms of Pseudomonas aeruginosa

Abstract: We investigated the relationship between the outer membrane protein OprD2 and carbapenem-resistance in 141 clinical isolates of Pseudomonas aeruginosa collected between January and December 2013 from the First Affiliated Hospital of Anhui Medical University in China. Agar dilution methods were employed to determine the minimum inhibitory concentration of meropenem (MEM) and imipenem (IMP) for P. aeruginosa. The gene encoding OprD2 was amplified from141 P. aeruginosa isolates and analyzed by PCR and DNA sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 15 publications
0
31
3
Order By: Relevance
“…Previous studies indicated that carbapenem resistance in Chinese P. aeruginosa isolates was driven mainly by a deficiency of OprD and may or may not be accompanied by the overexpression of MexAB-OprM or metallo-lactamase (MBL) production. 56,57 Although relatively uncommon among CRPA in China, with a proportion of 8.5%…”
Section: Page 17 Of 40mentioning
confidence: 99%
“…Previous studies indicated that carbapenem resistance in Chinese P. aeruginosa isolates was driven mainly by a deficiency of OprD and may or may not be accompanied by the overexpression of MexAB-OprM or metallo-lactamase (MBL) production. 56,57 Although relatively uncommon among CRPA in China, with a proportion of 8.5%…”
Section: Page 17 Of 40mentioning
confidence: 99%
“…In a study performed by Aki Hirabayashi et al (24). There was a direct relationship between the alteration or loss of oprD and the increase in MIC, for imipenem but not meropenem and other carbapenems (3,9,11). In a study conducted by Yumiko Sanbongi et al (25).…”
Section: Discussionmentioning
confidence: 99%
“…PCR and sequence analysis revealed an interpolation of a large fragment in the oprD gene were known as IS elements that are not observed in this study. Jilu Shen et al (9). Reported 96.5% (136/141) of the resistant isolates showed deletions or multi mutations that were driven loss or insertion of the oprD-encoding gene, 34 strains had a large deletion in the OprD gene, 6 isolates had IS, and 4 strains had no mutation and showed a normal OprD2 gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, OprD2 protein is able to form a specific locus by binding bacteria and carbapenems. It is one and only porin that allows antibiotics go through smoothly in current studies, especially for Pseudomonas aeruginosa (9). Therefore, loss or reduction in OMP OprD2 expression is an important mechanism leading to Pseudomonas aeruginosa resistance to carbapenem antibiotics.…”
Section: Discussionmentioning
confidence: 99%